2021
DOI: 10.1210/jendso/bvab048.1922
|View full text |Cite
|
Sign up to set email alerts
|

Lyme Disease: An Autoimmunity-Based “Destructive Thyroiditis” or Just Another “Non-Thyroidal Illness”?

Abstract: There is considerable evidence that some Borrelial (Lyme spirochetal) proteins share significant antigenic properties with several thyroid-related proteins (e.g. TSH receptor, thyroglobulin, thyroid peroxidase) and can induce thyroid autoimmunity, sometimes associated with Hashimoto’s thyroiditis and perhaps also a “destructive thyroiditis” such as “silent” thyroiditis or “Hashitoxicosis.” As an acute illness, Lyme disease may also constitute a “non-thyroidal illness” capable of perturbing thyroid function tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Paparone 15 described a case in which Lyme disease was superimposed on primary hypothyroidism and made the diagnosis of Borrelia infection challenging due to similar manifestations in both diseases. Dhliwayo et al 16 reported a case of a 22-year old woman with Lyme disease whose thyroid function tests were consistent with transient thyrotoxicosis and decreased radioiodine uptake in the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Paparone 15 described a case in which Lyme disease was superimposed on primary hypothyroidism and made the diagnosis of Borrelia infection challenging due to similar manifestations in both diseases. Dhliwayo et al 16 reported a case of a 22-year old woman with Lyme disease whose thyroid function tests were consistent with transient thyrotoxicosis and decreased radioiodine uptake in the thyroid.…”
Section: Discussionmentioning
confidence: 99%